Surfactant chemistry and polymer choice affect single-wall carbon nanotube extraction conditions in aqueous two-polymer phase extraction. (May 2022) - Sims, Christopher M.; Fagan, Jeffrey A.
Abstract: Quantitative determination of the effects of surfactant chemistry and polymer chain length on the concentration conditions necessary to yield extraction of specific single-wall carbon nanotube (SWCNT) species in an aqueous two-polymer phase extraction (ATPE) separation are reported. In particular, the effects of polyethylene glycol (PEG) chain length, surfactant ratios, and systematic structural variations of alkyl surfactants and bile salts on the surfactant ratios necessary for extraction were investigated using a recently reported fluorescence-based method. Alkyl surfactant tail length was observed to strongly affect the amount of surfactant necessary to cause PEG-phase extraction of nanotube species in ATPE, while variation in the anionic sulfate/sulfonate head group chemistry has less impact on the concentration necessary for extraction. Substitution of different bile salts results in different surfactant packings on the SWCNTs, with substitution greatly affecting the alkyl surfactant concentrations required for ( n, m ) extraction. Finally, distinct alkyl-to-bile surfactant ratios were found to extract specific ( n, m ) SWCNTs across the whole effective window of absolute concentrations, supporting the hypothesized competitive adsorption mechanism model of SWCNT sorting. Altogether, these results provide valuable insights into the underlying mechanisms behind ATPE-based SWCNT separations, towards further development and optimization of the ATPE method for SWCNT chirality and handedness sorting. Graphical abstract: TOC Alt. Text: Fluorescence of the (7, 5) single-wall carbon nanotube species is used to interrogate the competitive binding of sodium deoxycholate and alkyl-sulfate surfactants of different tail lengths to the nanotube surface, as the dominant surfactant controls the end phase of partitioning in aqueous two-polymer phase extraction separations. Image 1